A rare case of spontaneous severe haemoperitoneum in a primigravida in the third trimester: a case report - Sareen, Ravmeet Kaur; Anand, Payal; Sehgal, Chandni (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Spontaneous haemoperitoneum in pregnancy (SHIP) is a rare but potentially life-threatening obstetric emergency characterised by sudden, non-traumatic intraperitoneal bleeding, most commonly occurring in the third trimester and associated with significant maternal and perinatal morbidity and mortality. We report the case of a 23-year-old primigravid woman at 36+2 weeks’ gestation who presented with acute abdominal pain followed by fetal bradycardia and maternal haemodynamic instability. Emergency laparotomy revealed approximately 2 litres of haemoperitoneum with diffuse posterior uterine serosal bleeding in an intact uterus. Caesarean delivery was performed, and haemostasis was achieved using conservative surgical measures, including bilateral uterine artery ligation, allowing preservation of the uterus. Spontaneous haemoperitoneum should be suspected in pregnant women presenting with unexplained acute abdomen and fetal distress, as prompt diagnosis and early surgical intervention are critical for improving maternal and fetal outcomes.